Preserving the Past: A Dynamic Analysis of Heritage Tourism and Land Conservation in Mamluk Cairo - Amany E. Salem; Ahmed Tawhid Eissa; Thowayeb H. Hassan; Mahmoud I. Saleh (Heritage)
Historic urban cities face increasing pressure from tourism, necessitating sophisticated approaches to visitor management that protect both heritage values and local communities. The current study develops new sustainable metrics—sustainable visitor capacity (SVC) and Sustainable Visitation Index (SVI)—to provide a multifaceted assessment of heritage destination management beyond simple visitor volume calculations. The SVC considers operating hours, site capacity, and walking time, while the SVI holistically evaluates time efficiency, spatial distribution, and physical comfort. Applying these metrics to seven routes through the historic Mamluk monuments revealed significant variations in sustainability performance, with SVI scores ranging from 48.9 at Al-Ṣalῑba/Al-Sayyida Zaynab Streets to 92.8 at Northern Al-Mu’izz Street. The findings demonstrate that while the recommended daily visitor capacity ranges from 1286 to 2182 visitors across different routes, actual visitation frequently exceeds these thresholds, particularly in commercial zones. Geographic analyses and on-site studies identified the integration of tourist activities with commercial, residential, and religious uses as a critical factor contributing to overcrowding, especially evident in areas like Al-Ṣalῑba Street, where low SVI scores reflect challenges with unorganized markets and local congestion. The study offers site-specific recommendations for heritage managers, focusing on dynamic visitor management systems and zoning strategies that consider the dual function of these historic corridors as both tourist attractions and vital local thoroughfares. This research provides heritage managers with practical tools to quantify and enhance the sustainability of visitor experiences while preserving site integrity within complex urban heritage contexts.